The Complementarity of Crowdsourced Dictionaries and Professional Dictionaries viewed through the Filter of Neology - Franck Sajous; Amélie Josselin-Leray; Nabil Hathout (Lexis: Journal in English Lexicology)
This paper shows how amateur dictionaries, through their distinctive features (shorter inclusion timespan, analysis of the motivation, broad spectrum of expertise among the contributors) can complement professional dictionaries for the treatment of neologisms.